E-Learning Moodle SMK PGRI 1 TANGERANG - Didi Kurnaedi; Aep Gumiwa; Erna Oktora (Komunitas Dosen Indonesia, 2022)
Over the past 10 years, many educational institutions around the world have developed a variety of online learning media available to students. Online learning media makes the concept of educational institutions more flexible and resilient, especially in SMK PGRI 1 Tangerang. This research aims to create Moodle e-learning media to be used as learning media for SMK PGRI 1 Tangerang. The survey included data collected from 283 students, focusing on student and teacher perceptions of learning in Moodle. The data was processed using SPSS 26, and analysis of the data obtained revealed various factors associated with the implementation of Moodle's pedagogical, technical and managerial approach. The results show that people familiar with Moodle recognize the importance and usefulness of Moodle because it can be easily accessed from any web-enabled location. They are happy with Moodle and feel the importance of Moodle. Moodle also helps them better understand and learn subjects by changing the web content of the course, especially if students prefer the face-to-face method, but support online Moodle activities as the preferred method of learning.